ATRIBUTOS FÍSICO-HÍDRICOS DE UM CAMBISSOLO HÁPLICO ALUMÍNICO EM FUNÇÃO DE MODOS DE APLICAÇÃO DE CALCÁRIO - Auler, André Carlos (2014)
Liming is the practice used to correct soil acidity and its reaction is dependent on the mode of application of the lime. The addition of lime to the soil with the tilling is an alternative for increasing his reaction. However, tillage alters its structure and processes occurring in it. The aim of this study was to evaluate the influence of liming of liming in three modes of application of limestone (on the surface, incorporated with plowing and harrowing and subsoiling and disking) on the physico-hydrical attributes of a Dystrudept. For this, an experiment was installed in the field with banded design, with treatments in a factorial arrangement (3 × 2). Treatments formed from the combination of two rates of lime (0 and 15 Mg ha-1) and three modes of application of limestone (on the surface, incorporate with plowing and harrowing and subsoiling and harrowing). Undisturbed and disturbed soil samples were collected at 0-0.10 and 0.10-0.20 m layers between plant rows of corn 18 months after installation of the experiment. The water-dispersed clay (WDC), flocculation degree (FD), bulk density (BD), total porosity (TP), water retention curves, pore size distribution curve, particle size and soil chemical properties were determined order to diagnose the effects of liming the soil studied. Liming effects on the physico-hydrical attributes of the soil were restricted to 0-0.10 m layer. The WDC and the FD were influenced by tillage, but not by liming. When liming was performed on the surface, there was a reduction of the DB and increased TP. In all modes of application of limestone, liming increased water retention and altered the distribution of pores. To conclude, the changes in physico-hydrical attributes of the soil were mostly due to the increase of pH and replacement of aluminum by calcium and magnesium in the exchange complex.